2014
DOI: 10.1017/s1473550414000433
|View full text |Cite
|
Sign up to set email alerts
|

Are thermophilic microorganisms active in cold environments?

Abstract: The mean air temperature of the Icelandic interior is below 10 °C. However, we have previously observed 16S rDNA sequences associated with thermophilic lineages in Icelandic basalts. Measurements of the temperatures of igneous rocks in Iceland showed that solar insolation of these low albedo substrates achieved a peak surface temperature of 44.5 °C. We isolated seven thermophilic Geobacillus species from basalt with optimal growth temperatures of ~65 °C. The minimum growth temperature of these organisms was ~3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 34 publications
0
16
1
Order By: Relevance
“…Now, the question is how such cold environment (temperature never raises over 0°C) into which these thermophilic organisms are delivered could sustain their growth. Cockell et al (2015) suggested that, for an Icelandic rocky environment, temperature-induced niche differentiation may permit the presence of thermophilic organisms in a cold environment as well. In our case, these types of temperature differentiations are hardly expected, and no evidence of geothermal activity is known in the BC area.…”
Section: Discussionmentioning
confidence: 99%
“…Now, the question is how such cold environment (temperature never raises over 0°C) into which these thermophilic organisms are delivered could sustain their growth. Cockell et al (2015) suggested that, for an Icelandic rocky environment, temperature-induced niche differentiation may permit the presence of thermophilic organisms in a cold environment as well. In our case, these types of temperature differentiations are hardly expected, and no evidence of geothermal activity is known in the BC area.…”
Section: Discussionmentioning
confidence: 99%
“…A logical development of the first question is What adaptations have allowed microbes to persist in the planetary crust for over 3.5 billion years? Work we have undertaken that falls within this purview has included: (i) studies on the molecular (proteomic) responses of microbes to extreme conditions living within the planetary crust (Bryce et al, 2016 ); (ii) studies on the colonization of extreme volcanic environments (Kelly et al, 2014 ; Cockell et al, 2015b ); (iii) studies on habitats in impact craters (Pontefract et al, 2014 , 2016 ); and (iv) UKCA involvement, through science party membership, in the IODP (International Ocean Discovery Program) Expedition 364 to drill the peak ring of the Chicxulub impact crater (Morgan et al, 2016 ), linked to the end-Cretaceous mass extinction (Schulte et al, 2010 ). UKCA work in this project has been focused on understanding how impact craters produce habitats for deep subsurface life.…”
Section: Researchmentioning
confidence: 99%
“…(ii) studies on the colonization of extreme volcanic environments (Kelly et al, 2014 ; Cockell et al, 2015b );…”
Section: Researchmentioning
confidence: 99%
“…Such temporary nanoniches provide short-termed limited conditions for alkaliphilic thermophilic bacteria and therefore dictate fastened growth rate in order to cope with this limitation (Wiegel, 2002). Icelandic basaltic and rhyolitic glass and minerals in a sub-Arctic environment with the temperature range below required for thermophile activity were proposed to support transient growth of thermophiles in summer months (Cockell et al, 2015). The low albedo of these rocks has been suggested to facilitate their thermal conductivity and support the function of these igneous materials as microclimatic environments to harbor thermophilic microbial communities (Kelly et al, 2010(Kelly et al, , 2011Cockell et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Icelandic basaltic and rhyolitic glass and minerals in a sub-Arctic environment with the temperature range below required for thermophile activity were proposed to support transient growth of thermophiles in summer months (Cockell et al, 2015). The low albedo of these rocks has been suggested to facilitate their thermal conductivity and support the function of these igneous materials as microclimatic environments to harbor thermophilic microbial communities (Kelly et al, 2010(Kelly et al, , 2011Cockell et al, 2015). Apparently, these nanoniches inside the rock pores provide a certain potential for their temporary "re-awakening" of such communities during the warm periods.…”
Section: Introductionmentioning
confidence: 99%